Prevence zilní tromboembolické nemoci v pediatrii - Blatný, J (Vnitrni lekarstvi, 2006)
Data in Canadian registry for VTE in children show, that incidence of VTE in children is 0.07/10 000. The situation in adults--with incidence of VTE 37/10 000--is however completely different. Only 5% of VTE in children are idiopathic and less then 10% are related to hereditary prothrombotic risk factors only. In other words, more than 80% of VTE in children are somehow related to acquired prothrombotic risk factors. Despite of this, there have not been found any measures, that would be able to further decrease significantly this very low incidence of VTE in children. This is probably the reason, why to date there are no evidence based recommendations for primary prophylaxis of VTE in children and also there is no valid reason for non-selective screening for hereditary prothrombotic risk factors in population of children, who have not suffered VTE.
Keywords: Child; Thrombophilia; rizikové faktory; žilní trombóza; tromboembolie; Venous Thrombosis; Humans; trombofilie; lidé; Thromboembolism; dítě; Risk Factors